Cytotoxic and anti-migration activities of protein extracts from Trametes scopulosa (BERK.) Bres. mycelium against HCT 116 colon cancer cell line / Amal A. Rhaffor - Amal, A. Rhaffor (2017)
Colon cancer is one of the leading causes of cancer death. It is the third most common cancer in men and the second among women globally. Metastasis is a spread of cancer cells to distant locations in the body and usually occurs at stage IV of colon cancer. Distant metastasis is the principle cause of colon cancer deaths. It involves 6 main steps; local invasion, intravasation, circulation, extravasation, proliferation and angiogenesis. Polypore mushrooms have been investigated for its medicinal properties especially for anti-tumour activity. Trametes scopulosa is one of the polypore mushroom. However to date, no research concerning the anti-tumour effect of Trametes scopulosa has been published. This study is therefore aims to evaluate the anti-tumour potentials by looking at the cytotoxic and anti-migration activities of solvent and protein extracts from T. scopulosa (KUM70034) against colon cancer cell line (HCT 116). Pre-screening for cytotoxic activity against HCT 116 using MTT assay showed that all solvent extracts of T. scopulosa (methanol, hexane, dichloromethane and ethyl acetate) were deemed not actively cytotoxic against HCT 116 cells. However, all protein fractions obtained by ammonium sulphate precipitation at 30%, 60% and 90% (F30, F60 and F90) were actively cytotoxic against HCT 116 cells with fraction 60 exhibiting the most potent cytotoxicity (IC50 0.84±0.05 μg/mL). However, the fractions were not cytotoxic against normal lung fibroblast cell line (MRC-5). F60 that contained the highest protein level of 459.745±17.55 μg/mL was separated into a few single bands corresponding to a molecular weight ranging from 12 kDa to 64 kDa. Subsequently, F60 was evaluated for cytotoxicity against HCT 116 and MRC-5 cells at 20 μg/mL protein concentration. Results showed that the F60 of T. scopulosa when tested by protein content was indeed cytotoxic against HCT 116 cells with IC50 value of 0.57±0.06 μg/mL protein but showed no cytotoxic effect against MRC-5 cells. The in vitro scratch wound assay was used to measure inhibition of cellular migration activity. The HCT 116 cells treated with F60 slowed down the migration activity of the cells as compared to the control group (non-treated cell line). The fraction was further purified by anion exchange chromatography and collected fractions (P1, P2 and P3) were retested for cytotoxic and anti-migration activities. Results showed that P2 and P3 fractions had better cytotoxic and anti-migration effects against HCT 116 cell line as compared to P1. However, the cytotoxic effects of both fractions were lower than the partially purified protein (F60). The P2 and P3 fractions were then further evaluated for synergism study. Results showed that, the cytotoxic effect of the combine mixture at a ratio of 1:1 was greater than F60. This suggests that P2 and P3 fractions have synergistic cytotoxic effect. Both fractions were then subjected to protein analysis using LCMS Q-TOF. Two proteins were characterized as pyranose-2-oxidase and carboxylic ester hydrolase. Two uncharacterized proteins were also found. However, only pyranose-2-oxidase has potential as anti-tumour effect against HCT 116 cancer cells. As a conclusion, this study suggests that proteins from mycelial extract of T. scopulosa could potentially to be used as an anti-tumour agent against colon cancer cells.